Rāsa theory in modern era : an application of classical Indian philosophy to film - Low, Nicole Emma (Nanyang Technological University, 2021)
This paper makes a case for the application of classical Indian aesthetics in explaining the experience of film. This is important as classical Indian aesthetics does not pale in comparison to Western theory, possessing its own merits yet suffers from under-representation. By showing that classical Indian aesthetics is on par with Western aesthetics, a gap between the two cultures and traditions is bridged. I argue how classical Indian aesthetics is able to offer insight into the emotional aspect of aesthetic experience which is limited in Western thought. After which, I introduce the Nāṭya-śāstra and the theory of rāsa in order to show how it explains the aesthetic experience in film. The view that I ultimately propose is that the rāsa theory is applicable in enriching the understanding of films that fall under the category of the ‘spectacle’.